Application Of Appropriate Technology Automation Systems For Making Martabak Manis Machine For Capacity Building In MSMEs In The Gresik Region - Nugroho, Andianto Wahyu; Riyadi, Slamet; Siswadi, Siswadi; Setyono, Gatot; Nugroho, Wahyu (Pengabdian Masyarakat dan Inovasi Teknologi (DIMASTEK), 2023)
Martabak is a snack that is often sought after by the general public. Therefore, martabak is a commodity with prospects to develop as an industrial business. Martabak's selling business is one type of business that has the potential to be developed. So many business people are interested in selling this type of food. This business does not require significant capital but has a sizable profit known as bright moon. Sweet martabak has main ingredients, including flour, eggs, water, sugar, and leavening dough agent; there is also the addition of juice. The existence of this machine is expected to increase the quality and quantity of products because there are still many small entrepreneurs in the Gresik area who use traditional tools and carry out a moving process that takes quite a lot of time and effort. Hence, the author now makes a sweet martabak machine with a 25 kg/hour capacity to increase production, quality, and quantity with maximum results for MSMEs in the Gresik area.